2020
DOI: 10.1016/j.psj.2020.07.049
|View full text |Cite
|
Sign up to set email alerts
|

Medium-chain α-monoglycerides improves productive performance and egg quality in aged hens associated with gut microbiota modulation

Abstract: The present study aimed to evaluate the effects of medium-chain α-monoglycerides ( MG ) on productive performance, egg quality, serum biochemical indices, and gut microbiota in laying hens. A total of 252 40-wk-old Hy-Line Brown laying hens were randomly allotted into two groups (21 hens per replicate, 6 replicates per group) and fed with a basal diet (CON group) or a basal diet containing 300 mg/kg of MG (MG300 group). The eggs laid were recorded daily on a replicate basis, and egg qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 43 publications
1
19
0
2
Order By: Relevance
“…There is growing evidence that medium-chain fatty acid glyceride-based food additives can modulate the gut microbiota in mice and affect their health [ 14 , 15 , 16 , 17 , 18 ]. Originally, GMC was a medium-chain fatty acid glyceride food preservative.…”
Section: Discussionmentioning
confidence: 99%
“…There is growing evidence that medium-chain fatty acid glyceride-based food additives can modulate the gut microbiota in mice and affect their health [ 14 , 15 , 16 , 17 , 18 ]. Originally, GMC was a medium-chain fatty acid glyceride food preservative.…”
Section: Discussionmentioning
confidence: 99%
“…At the phylum level, the gut microbiota of chickens includes hundreds of species, including microbial species dominated by Firmicutes, Bacteroides , Proteobacteria, and Actinomycetes [ 65 , 66 ]. Oil additives such as α-linolenic acid (ALA), DHA, and glycerin and its derivatives (such as glycerol monocaprylate and glycerol monolaurate) exert a positive effect on the intestinal microbial composition, egg production performance, egg quality (e.g., egg weight and egg yolk FA composition), reproductive performance, and body health of laying hens, which indicates the potential role of dietary oils in improving the microbial community, lipid metabolism, and health of laying hens [ 67 , 68 , 69 , 70 ]. For example, studies have found that the addition of linseed oil and algae oil to the diet increases the types of Firmicutes (such as Faeculus , Clostridium, and Ruminococcus ) microorganisms, and these microorganisms are closely related to FA metabolism [ 68 , 69 ].…”
Section: Mechanism Underlying the Effects Of Dietary Oils On The Production Performance And Egg Quality Of Laying Hensmentioning
confidence: 99%
“…8 Inclusion of GML and glycerol monodecanoate (GMD) mixture in the diet of aged hens improves egg-laying performance, feed efficiency and egg quality associated with gut microbiota modulation. 24 The gut microbiota alteration of mice by different dosages of GML supplementation may exert a different effect on systemic low-grade inflammation, glucose and lipid metabolism. 25,26 Our previous studies demonstrated that regulation of gut microbiota and its metabolites by dietary GML and MG mixture (GML and GMD) showed a close positive relationship with the enhanced productive performance, feed utilization, and meat and egg quality of poultry.…”
Section: Introductionmentioning
confidence: 99%